he Relation-Ship between Phytoalexin Production in Plant and Plant Resistance to Fungal Infection. - Nokhalan, Abdulazeez M (Al-Nahrain Journal of Science, 2013)
The phytoalexin accumulation in the leaves and whole plants of two cultivators of Alfalfa plants, resistant and susceptible to the fungus Verticillium albo-atrum isolates (V1) Virulent and (V2) AVirulent and many species were investigated, the results showed that different isolates and species of Verticillium fungus induce the resistant and susceptible cultivar of Alfalfa to produce different amount of phytoalexin. But the two cultivars produce similar amount of phytoalexin in response to either pathogenic isolates (V1) or the non pathogenic isolates (V2).